1974
DOI: 10.2337/diab.23.4.293
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes of Glucose Metabolism in Liver of Subjects with Adult-onset Diabetes

Abstract: An enzyme study was made on needle biopsy specimens of liver from thirty-two subjects with adult-onset diabetes and normal body weight and thirty-two controls. The enzyme pattern in the patients with diabetes was different from that seen with alloxan diabetes. The activities of the two glucose phosphorylating enzymes tested were changed in opposite directions, hexokinase being enhanced and glucokinase moderately decreased. Total glucose phosphotransferase activity remained unchanged. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
3

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
3
5
0
3
Order By: Relevance
“…The patterns of hepatic enzymes in the spontaneous diabetes rats are similar in some aspects to those in the human adult-onset diabetic patients as reported by Belfiore et al (1974). In this sense the spontaneous diabetes rats produced by repetition of selective breeding may be a useful experimental model for diabetes mellitus.…”
Section: Gluconeogenic Enzymessupporting
confidence: 74%
See 1 more Smart Citation
“…The patterns of hepatic enzymes in the spontaneous diabetes rats are similar in some aspects to those in the human adult-onset diabetic patients as reported by Belfiore et al (1974). In this sense the spontaneous diabetes rats produced by repetition of selective breeding may be a useful experimental model for diabetes mellitus.…”
Section: Gluconeogenic Enzymessupporting
confidence: 74%
“…For instance, Belfiore et al (1974) reported that in the liver of the diabetic patients the hexokinase activity was increased while the glucokinase activity was moderately decreased, the activity of phosphofructokinase was reduced suggesting a diminished glycolysis, the activity of In contrast, changes in activities of the enzymes in glucose metabolism occurring in rats with alloxan diabetes have been well defined, i.e., a decrease in glucokinase and an increase in key gluconeogenic enzymes including glucose -6-phosphatase, phosphoenolpyruvate carboxykinase and pyruvate carboxylase (Belfiore et al 1974). In the liver of diabetic rats, glucose uptake and its utiliza tion are decreased, while gluconeogenesis and glucose output from the liver are enhanced (Belfiore et al 1974). …”
Section: Wistarmentioning
confidence: 99%
“…Alternatively, greater production of glucose-6-phosphate through the activity of hexokinase might explain an increase in GC activity. Indeed, a significant increase in hexokinase activity was reported in the studies of Belfiore et al (24). However, the method used to determine GK activity in the present studies involves the subtraction of hexokinase activity (glucose-6-phosphate generated at 0.5 mmol/l glucose) from total glucose phosphorylation.…”
Section: Discussionmentioning
confidence: 61%
“…Using this method, we demonstrated an increase in G6Pase activity and a decrease in GK activity in diabetic subjects in whom EGP was also elevated. In one of the few studies of this topic published (24), no difference in G6Pase activity was observed between diabetic and nondiabetic subjects. However, use of whole liver homogenates rather than microsomal preparations and failure to account for nonspecific phosphatase activity may have masked the differences in these studies.…”
Section: Discussionmentioning
confidence: 90%
“…GK was purified from control and type 2 diabetic human liver tissues and the purified GK consisted of single polypeptide chain with molecular weight of 50 kDa. The activity of purified GK was taken as standard to compare with the enzyme activity in the type 2 diabetic patient where decreased enzymatic activity and increased K m was observed (Table ) . It is very well known that glucose is highly specific substrate for GK; therefore, comparing the kinetics, we can deduce the variations in the catalytic property of GK using glucose as substrate.…”
Section: Discussionmentioning
confidence: 99%